2016
DOI: 10.1063/1.4971818
|View full text |Cite|
|
Sign up to set email alerts
|

The role of defects in the electrical properties of NbO2 thin film vertical devices

Abstract: Epitaxial NbO2 thin films were grown on Si:GaN layers deposited on Al2O3 substrates using pulsed laser deposition. Pulsed current-voltage (IV) curves and self-sustained current oscillations were measured across a 31 nm NbO2 film and compared with a similar device made from polycrystalline NbO2 film grown on TiN-coated SiO2/Si substrate. Crystal quality of the as grown films was determined from x-ray diffractometry, x-ray photoelectron spectroscopy and atomic force microscopy data. The epitaxial film device was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…For currents measured at the same voltage, for example at 0.2 V, the film grown in lower growth pressure (1 mTorr) had a current that was an order of magnitude higher than the one measured on the film grown in higher growth pressure (10 mTorr). The larger content of Our previous study of NbO2 lateral devices 19,20 demonstrated that the current switching was caused by Joule heating from the current flowing through the devices. Prior to observing a threshold switching, a forming pulse was needed, requiring the application of larger electric field magnitudes than those used during normal operation.…”
Section: Effects Of Nb 5+ /Nb 4+ Contentmentioning
confidence: 94%
See 2 more Smart Citations
“…For currents measured at the same voltage, for example at 0.2 V, the film grown in lower growth pressure (1 mTorr) had a current that was an order of magnitude higher than the one measured on the film grown in higher growth pressure (10 mTorr). The larger content of Our previous study of NbO2 lateral devices 19,20 demonstrated that the current switching was caused by Joule heating from the current flowing through the devices. Prior to observing a threshold switching, a forming pulse was needed, requiring the application of larger electric field magnitudes than those used during normal operation.…”
Section: Effects Of Nb 5+ /Nb 4+ Contentmentioning
confidence: 94%
“…Our previous study of NbO2 lateral devices 19,20 demonstrated that the current switching was caused by Joule heating from the current flowing through the devices. Prior to observing a threshold switching, a forming pulse was needed, requiring the application of larger electric field magnitudes than those used during normal operation.…”
Section: Effects Of Nb 5+ /Nb 4+ Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…A Si-doped GaN (5 µm)/AlN (300 nm)/Al 2 O 3 (430 µm) wafer, provided by PI-KEM, was used as a substrate for thin film growth. 31 The schematic of the series circuit for the device under test is shown in Fig. 1 insulating to metallic phase.…”
mentioning
confidence: 99%